Mechanical and thermo-mechanical properties of carbon nanotube reinforced composites - Dong, Jonathan (Taylor and Francis, 2014)
A study on the mechanical and thermo-mechanical properties of carbon nanotube (CNT) reinforced nanocomposites is presented in this article. Mori-Tanaka method is used for modeling the effective stiffness and coefficient of thermal expansion. Regression formulas were developed to describe the effects of CNT orientation, aspect ratio, and CNT volume fraction. Given the statistical distributions of CNT orientations and aspect ratios, the effective properties can be conveniently derived by numerical integration using these formulas.